Development and verification of a highly accurate and precise passing machine for american football - Hollaus, B.; Raschner, C.; Mehrle, A. (Proceedings, 2020)
Passing a ball is a central aspect in the game of American Football. However, current passing machines do not fulfill the high quality standards for adequate catch training. The goal was to realize a passing machine that could do precise and accurate passes in a fully automated way in order to create high quality automated catch training. Automation was carried out to a degree that the release angle in terms of azimuth and elevation, release velocity and the release spin of the ball could be controlled via a wireless device within a reasonable range. Additionally, a pass prediction model was developed to determine where the pass went to and which height to catch it by least squares fit of 225 sample points with a second order function (R2>0.99). Normalized precision and accuracy of the machine were verified in an experiment with precision being less than 1% and accuracy less than 3% for more than 90% of all relevant passes.